Effect of Mineral Supplementation and Dewormer on Service Period and Milk Production in Buffaloes under Field Conditions - Rathore, R S; Verma, R K; Dayanand, Dayanand; Mehta, S M (Annals of Arid Zone, 2017)
An on farm testing was conducted to assess the effect of mineral supplementation and dewormer on service period and milk production of buffaloes under field condition. Twenty four lactating buffaloes of almost same stage of lactation and from II to IV parity were selected for three consecutive years in three randomly selected villages. They were divided into three groups, having 8 in each group. First group was supplemented by mineral mixture @ 50 gms day-1 for 50 days + dewormer (Fenbendazole) two times at 21 days interval (T1); second group supplemented by Cu-Co tablets @ 5 day-1 for 10 days + Janova capsule (an Ayurvedic heat inducer) @ 3 day-1 for 5 days and dewormer (Fenbendazole) two times at 21 days interval (T2) and third group served as control (farmers practice) [T3]. Results revealed that the average service period was 81.2±2.0 days, 96.8±2.5 days and 117.6±3.2 days for treatment T1, T2 and T3, respectively. Treatment T1 reduced 36.5 days (31.0%) service period and T2 reduced 20.8 days (17.7%) in comparison to control group (T3). Treatment T1 had significant effect on service period over treatment T2 and T3. Treatment T2 also had significant effect on service period over control group. The average milk production was 8.90, 8.15 and 7.12 liter day-1 for treatment T1, T2 and T3, respectively. Treatment T1 had significant effect on milk production in comparison to control group i.e. farmers practice but it was statistically at par with treatment T2. The net profit from sale of extra milk was Rs. 37.52 and Rs. 21.32 with B:C ratio 1:7.22 and 1:6.27 for treatment T1 and T2, respectively. It can be concluded that mineral supplementation and deworming gave better performance in reducing the service period as well as increasing the milk production of buffalo.